Analisis Strategi Dosen dalam Membentuk Karakter Keagamaan Mahasiswa di Institut Agama Islam Qomarul Huda Bagu - Murdianto Murdianto (LP. Ma'arif Janggan Magetan, 2024)
This research aims to analyze the strategies used by lecturers in forming the religious character of students in the tertiary environment. The research method used is Systematic Literature Review (SLR), data was obtained through systematic searches in academic databases such as PubMed, Google Scholar, and ProQuest, relevant articles were filtered and analyzed to identify patterns of strategies implemented by lecturers. The research results show that interactive approaches, the use of case studies, extracurricular activities, and personal coaching are some of the strategies commonly used by lecturers. Although these strategies have proven effective in shaping students' religious character, challenges such as religious plurality among students and the influence of popular culture highlight the need to develop more inclusive and adaptive strategies. The implications of this research are to provide practical guidance to universities and lecturers in increasing the effectiveness of religious learning and provide a basis for developing approaches that are more responsive to the religious and spiritual needs of students in higher education.